Factors Contributing to Prolonged Time to Extubation After Sevoflurane Anesthesia in Pediatric Patients who Underwent Strabismus Surgery: A Retrospective Study - Kyung Mi Kim; Ki Hwa Lee; Jae Hong Park; Ji Yeon Kwon; Yei Heum Park; Jae Hwan Kim (Bali Journal of Anesthesiology)
Background: Rapid and smooth emergence is a crucial factor in the recovery of pediatric patients, especially after short ambulatory surgery. However, the factors contributing to the recovery time in pediatric patients after sevoflurane anesthesia have not yet been established. The present study evaluated the underlying factors affecting prolonged extubation time after sevoflurane anesthesia administration. Materials and Methods: Data were collected retrospectively from pediatric patients who underwent strabismus surgery between January 2011 and December 2020. Variables affecting time to extubation, including patient-related, anesthesia-related, and procedure-related factors, were investigated for univariate logistic and multivariate logistic regression analyses. Results: Overall, 459 patients were included in the final analysis. In the univariate analysis, the timing of fentanyl administration (P = 0.001), fentanyl dosage (P = 0.036), and operation/anesthesia duration ratio (P < 0.001) was found to prolong the extubation time significantly. Multiple logistic regression analysis that included intraoperative factors showed that late IV fentanyl administration (odds ratio [OR] = 3.051; 95% confidence interval [CI] = 1.830–5.086), use of a high (>1 µg/kg) fentanyl dose (OR = 2.61; 95% CI = 1.383–4.910), and a low operation/anesthesia duration ratio (OR = 0.92; 95% CI = 0.904–0.945) were associated with late recovery time. Conclusion: Late fentanyl administration, use of a high fentanyl dose, and a low operation/anesthesia duration ratio are potential risk factors for prolonged extubation time after sevoflurane anesthesia administration in pediatric patients.